Analisis Indeks Kualitas Tanah di Lahan Kering Kabupaten Aceh Besar Provinsi Aceh - Lukman Martunis; Sufardi Sufardi; Muyassir Muyassir (Universitas Pattimura, 2016)
Soil quality is ability of soil to preserve the productivity of pants, preserve maintain water supplies, and support human activities. The soil quality cannot be directly measured therefore physical, chemical and biological indicators collectively are determined which influence the soil quality called minimum data set (MDS). A study and experimental analysis was conducted in June - November, 2015. The descriptive study was done in some types of mineral dry soil in Aceh Besar by measuring its soil index quality using Mausbach and Seybold (1998) criteria which has been modified by Partoyo (2005). The soil quality index was analyzed using function that represented most of the soil. The soil samples were taken by purposive sampling and the texture, volume weight, porosity, C-organic, pH, P-available, K-exchangeable, N-total and rooting depth were analyzed in laboratories. Soil quality index values ranged between 0-1. The higher index value indicates better quality. The analysis result of selected soil functions (MDS) and MDS scores were than summed to determine the value of the soil quality index (SQI). The study concludes that the three types of soil classified as â€œgoodâ€ are Andosol Umbric (Typic Hapludands), (SQI = 0.7903), Cambisol Distric (Typic Dystrudepts), (SQI = 0.7241), Aluvial Eutric (Typic Eutrudept), (SQI = 0.6638) while the three other types of soil classified as â€œmoderateâ€ are Litosol (Lithic Udorthens), (SQI = 0.5471), Cambisol Eutric (Typic Eutrudepts), (SQI = 0.5361), and Podsolic Haplic (Typic Hapludults), (SQI = 0.4712).